2000
DOI: 10.1590/s1516-31802000000600003
|View full text |Cite
|
Sign up to set email alerts
|

Is intra-operative gamma probe detection really necessary for inguinal sentinel lymph node biopsy?

Abstract: a b s t r a c tCONTEXT: Sentinel node (SN) biopsy has changed the surgical treatment of malignant melanoma. The literature has emphasized the importance of gamma probe detection (GPD) of the SN. OBJECTIVE:Our objective was to evaluate the efficacy of patent blue dye (PBD) and GPD for SN biopsy in different lymphatic basins. DESIGN:Patients with cutaneous malignant melanoma in stages I and II were submitted to biopsy of the SN, identified by PBD and GPD, as part of a research project. SETTING:Patients were seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…Previous study had suggested similar results. 16 Lymphoscintigraphy has a crucial role in localizing the SN basin and allowing skin localization of the SN. In case of inguinal sentinel node, deep pelvic and popliteal SN has to be checked by lymphoscintigraphy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study had suggested similar results. 16 Lymphoscintigraphy has a crucial role in localizing the SN basin and allowing skin localization of the SN. In case of inguinal sentinel node, deep pelvic and popliteal SN has to be checked by lymphoscintigraphy.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of thin melanoma has increased as compared to more deeply infiltrating lesions (1)(2)(3). Sentinel node (SN) biopsy proved to be an accurate staging procedure of regional nodal status with minimal morbidity and SN status is the most important prognostic factor for localized melanoma (4,5).…”
mentioning
confidence: 99%
“…[5][6][7] In 1993, Alex et al 8 injected technetium and introduced the technique of gamma probe-guided surgery to identify the sentinel node. In the same year, Krag et al 9 published a study on sentinel node using Technetium-99 (Tc99) associated with the use of probes for detection of gamma rays in breast cancer.…”
Section: Introductionmentioning
confidence: 99%